Introduction to the Scandinavian Organizational Studies - Christensen, Søren; Sevón, Guje; Tainio, Risto; Greve, Arent; RonessPaul G.; Czarniawska, Barbara (Journal of Economic Sociology, 2010)
Detailed description in the text